Use of impulse ventilation for smoke control in underground car parks - Viegas, J. (2009)
Traditional methods for smoke control in underground car parks are based on the undisturbed thermal stratification of smoke and its exhaust to the outside. Usually walls and smoke barriers are used to avoid the flow of the smoke to other spaces. Impulse ventilation systems (IVS) are currently applied to the smoke control in underground car parks and it is able to avoid the smoke spread. This paper will present the principles for the use of IVS for smoke control in underground car parks illustrated with the results of CFD simulations. The paper will detail the physical processes of smoke entrainment by impulse fan jet, interaction of impulse fan jet with smoke ceiling jet, the necessary distance between impulse fans and the required exhaust flow rate from these compartments.